Knowledge of, and Attitudes Toward, Concussion in Japanese Male Collegiate Athletes - Suzuki, Keita; Imamoto, Takashi; Nagai, Satoshi; Takemura, Masahiro (Frontiers in Sports and Active Living, 2022)
Japan has no streamlined concussion education for collegiate athletes, and guidelines vary by sport. In particular, research on knowledge of, and attitudes toward, concussion is necessary for the establishment of concussion education for Japanese collegiate athletes. The aim of the present study was to assess the knowledge of, and attitudes toward, concussion in Japanese male collegiate athletes and to investigate their experiences with suspected concussion symptoms. An online questionnaire was administered to 390 collegiate athletes participating in the following five sports with a high incidence of concussion: rugby union, soccer, basketball, American football, and judo. Of the 121 valid responses, 91 (77.1%) indicated that they had experienced suspected concussion symptoms at least once and 46 of these 91 respondents had not reported their symptoms of suspected concussion at least once. Athletes who had never experienced concussion symptoms were significantly less likely to recognize the symptoms of concussion (p < 0.001). Most athletes recognized headache and dizziness as suspected concussion symptoms. However, the recognition rate for several symptoms was lower than the prevalence of these symptoms as shown in previous studies. This suggests that educational initiatives might be important to bridge the gap between athletes' knowledge and understanding of frequently occurring concussion symptoms and to improve reporting behavior.